REKONSTRUKSI KOMUNIKASI SOSIAL SEBAGAI UPAYA PENCEGAHAN COVID-19 DI INDONESIA - Mubin, Mubin M (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 16 No 2 (2020)DO - 10.24239/al-mishbah.Vol16.Iss2.210, 2020)
This study aims to provide an educational tool by presenting the problem of handling Covid-19 in Indonesia as well as efforts to unite the community through the reconstruction of social communication to minimize conflicts during the pandemic. The subject of this research includes the realization of the prevention of Covid-19 in Indonesia, social problems in the pandemic era, and reconstruction of social communication as an effort to prevent viruses in society. The research method used is a comparative study learning experience as a medium for data analysis with literature review. The results of this study concluded that efforts to deal with covid-19 in Indonesia were a strategic step but not yet massive so that the number of covid-19 transmissions has increased significantly. Among the causes; weak regulatory discipline, covid-19 information is ambiguous and there is a prejudice oriented towards economic and political interests. These problems can be prevented by reconstructing social communication with structural, cultural, and dialogue approaches.